The Comfort Women : Sex Slaves of the Japanese Imperial Forces - Hicks, George (Singapore Heinemann Asia, 1995)
Over 100,000 women across Asia were victims of enforced prostitution by the Japanese Imperial Forces during World War II. Until as recently as 1993 the Japanese government continued to deny this shameful aspect of its wartime history. George Hicks's book is the only history in English regarding this terrible enslavement of women.
Include Illustrations, Bibliography and Index.
Keywords: Women -- World War (1939-1945) -- Comfort women -- Asia -- Atrocities -- Service, Compulsory non-military -- Sino-Japanese War (1937-1945) -- Japan